1995
DOI: 10.1161/01.cir.92.5.1246
|View full text |Cite
|
Sign up to set email alerts
|

Myocardial Kinetics of a Putative Hypoxic Tissue Marker, 99m Tc-Labeled Nitroimidazole (BMS-181321), After Regional Ischemia and Reperfusion

Abstract: Thus, acute regional ischemia in these studies was visualized as an increase in retention of BMS-181321, suggesting its applicability in the imaging of clinical conditions of myocardial hypoperfusion.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

1996
1996
2017
2017

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(7 citation statements)
references
References 12 publications
0
7
0
Order By: Relevance
“…1 Although studies have suggested retention of these radiocompounds by ischemic myocardium, their use has been limited by extensive hepatic uptake, low cardiac specificity, and low target-to-background uptake of tracer. 1,25,26 For example, only 0.008% of an intracoronary injection of a 99m Tc-labeled nitroimidazole was retained per gram of ischemic porcine myocardium, 26 which is lower than the ischemic skeletal muscle retention of our intravenously injected VEGF 121 . This may be due in part to the threshold requirement of extremely low oxygen tensions before these compounds are retained.…”
Section: Comparison With Previous Studiesmentioning
confidence: 85%
See 1 more Smart Citation
“…1 Although studies have suggested retention of these radiocompounds by ischemic myocardium, their use has been limited by extensive hepatic uptake, low cardiac specificity, and low target-to-background uptake of tracer. 1,25,26 For example, only 0.008% of an intracoronary injection of a 99m Tc-labeled nitroimidazole was retained per gram of ischemic porcine myocardium, 26 which is lower than the ischemic skeletal muscle retention of our intravenously injected VEGF 121 . This may be due in part to the threshold requirement of extremely low oxygen tensions before these compounds are retained.…”
Section: Comparison With Previous Studiesmentioning
confidence: 85%
“…This may be due in part to the threshold requirement of extremely low oxygen tensions before these compounds are retained. 26 …”
Section: Comparison With Previous Studiesmentioning
confidence: 99%
“…ROI analyses yielded an ischaemic H/Lu ratio of 1.7 for 99m TcO(BAT-NI); the corresponding ratios for HL91 [21] and for BMS-181321 [5] were approximately twofold higher. The ischaemic H/Li ratio of 99m TcO(BAT-NI) is comparable to that of HL91 [21] and at least twofold higher than reported for BMS-181321 [3,5]. The ischaemic tissue contrast of the 99m TcO(BAT) tracers on planar images does not seem ideal for clinical use.…”
Section: Discussionmentioning
confidence: 99%
“…The high costs and limited availability of positron emission tomography (PET) systems, however, have spurred the search for nitroimidazole derivatives suitable for labelling with single-photon emitters. The most widely investigated compound, 99m TcO(PnAO-1-(2-nitroimidazole)) (BMS-181321), was taken up in ischaemic myocardium in vivo [3,4,5]. However, the high hepatic uptake of this tracer has made its clinical use questionable [3].…”
Section: Introductionmentioning
confidence: 99%
“…Imidazoles can be labeled with 99m Tc and potentially used to localize in areas of low oxygen tension during severe ischemic episodes [26].Therefore, these agents may have a potential role in the evaluation of acute chest pain. Several experimental studies have shown significant regional uptake of investigational nitroimidazoles in areas of low flow and demand ischemia [27][28][29][30]. Further study of these agents will be necessary to assess the degree of ischemia necessary to produce a sufficient decrement in tissue oxygen tension and subsequent retention of tracer.…”
Section: Nitroimidazolesmentioning
confidence: 99%